Grading practices, gender bias and educational outcomes: evidence from Italy. Issue 5 (3rd September 2022) - Di Liberto, Adriana; Casula, Laura; Pau, Sara
ABSTRACT: We study if the Italian school system suffers from gender bias when judging students. To this aim, we use a differences-in-differences approach that compares the teachers' assessments and the standardized test scores that the students receive during the school year. We have census data for all Italian fifth and sixth graders in two different subjects, math and language, that include a rich set of additional controls. Our evidence reveals that, since primary school, boys are graded less favourably than girls in both math and language. This result is also confirmed for middle school students (sixth graders), and it holds even when (a) we separate the analysis between the most and least developed Italian regions, (b) we control for possible gender-specific attitude towards cheating and teachers' manipulation and (c) we introduce class and school fixed effects in the models. Comparing the results obtained across different levels of schooling and subjects, we cannot clearly identify the role of specific mechanisms in determining the gender bias. Overall the analysis suggests further study on the role of teachers' characteristics.